2013
DOI: 10.3390/atmos4030299
|View full text |Cite
|
Sign up to set email alerts
|

Failure and Redemption of Multifilter Rotating Shadowband Radiometer (MFRSR)/Normal Incidence Multifilter Radiometer (NIMFR) Cloud Screening: Contrasting Algorithm Performance at Atmospheric Radiation Measurement (ARM) North Slope of Alaska (NSA) and Southern Great Plains (SGP) Sites

Abstract: Well-known cloud-screening algorithms, which are designed to remove cloud-contaminated aerosol optical depths (AOD) from Multifilter Rotating Shadowband Radiometer (MFRSR) and Normal Incidence Multifilter Radiometer (NIMFR) measurements, have exhibited excellent performance at many middle-to-low latitude sites around world. However, they may occasionally fail under challenging observational conditions, such as when the sun is low (near the horizon) and when optically thin clouds with small spatial inhomogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…With all this in mind, we find that the variability of the optical depth (which is intended to reflect the variability in the atmosphere, although we cannot rule out some contribution from the instrument's noise when the signal is very low) is not sufficient to discriminate between cloud and aerosol. The optical depth itself and its wavelength dependence (AE) do not help very much in this distinction (despite that Kassianov et al 2013 suggested a method that worked well for their Arctic site). Figure 8 shows the histograms of the populations of points screened out as clouds (this is for Girona, so 88,000 points), points that passed the strict filter so they are considered aerosol (39,000), and points that belong to the transitional zone (81,000), as a function of OD and AE.…”
Section: Mfrsr Estimations Of Od and Ae And Cloud Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…With all this in mind, we find that the variability of the optical depth (which is intended to reflect the variability in the atmosphere, although we cannot rule out some contribution from the instrument's noise when the signal is very low) is not sufficient to discriminate between cloud and aerosol. The optical depth itself and its wavelength dependence (AE) do not help very much in this distinction (despite that Kassianov et al 2013 suggested a method that worked well for their Arctic site). Figure 8 shows the histograms of the populations of points screened out as clouds (this is for Girona, so 88,000 points), points that passed the strict filter so they are considered aerosol (39,000), and points that belong to the transitional zone (81,000), as a function of OD and AE.…”
Section: Mfrsr Estimations Of Od and Ae And Cloud Screeningmentioning
confidence: 99%
“…For example, the difficulties in trying to distinguish clouds and aerosol in sunshine duration records have been pointed out elsewhere (Sanchez-Romero et al, 2014). In addition, many works focus on removing cloud -contamination‖ from aerosol observations performed with sunphotometers or shadowband radiometers (Alexandrov et al, 2004;Kassianov et al, 2013;Michalsky et al, 2010). The problem further expands when considering other views (satellite) or other wavelengths (ceilometers in the infrared, microwave radiometers, weather radars).…”
Section: Introductionmentioning
confidence: 99%
“…The parameter is adjusted to be conservative; that is, it tends to identify some AODs as being contaminated, when in fact they are not, thereby embracing the philosophy that it is better to error on the side of removing a few good AODs rather than letting a significant number of cloud contaminated AODs slip through. Threshold values used in the VAP were derived following the procedures described in Kassianov et al (2013). Figure 9 shows the cloud screen applied to the AODs.…”
Section: Application Of a Cloud Screenmentioning
confidence: 99%
“…The blue dots in this are the AODs that have been screened, and deemed acceptable, whereas the red dots show "AODs" that are likely to be cloud contaminated. For additional cloud screening considerations, see Kassianov et al (2013).…”
Section: Application Of a Cloud Screenmentioning
confidence: 99%